Efektivitas Model Problem Based Learning pada Keterampilan Menulis Teks Iklan Siswa Kelas VIII SMP Negeri 5 Mandai - Tasik, Meisya Bura; Sultan, Sultan; Saleh, Muhammad (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to describe advertising text writing skills using problem based learning and project based learning models and test the effectiveness of the problem based learning model on the advertising text writing skills of class VIII students at SMP Negeri 5 Mandai. The design of this research is quasi experimental. The research sample consisted of 124 students who were grouped into experimental and control classes. The instrument of this research is a test consisting of an initial test and a final test. The data analysis technique used is descriptive and inferential analysis in the form of normality tests, homogeneity tests and hypothesis tests. The results of this research show that the average score of students using the problem based learning model was 82.09. Meanwhile, the project based learning model obtained 73.54. Although, both are in the